Factors associated with academic motivation in nursing students: A cross-sectional study - Tuan Van Nguyen; Wantonoro Wantonoro; Huynh Xuan Thi Nguyen; My Ngoc Thi Huynh; Manh Truc Huynh Nguyen; Minh Quang Le; Thu Minh Vo; Loc Van Huynh; Phuong Viet Nguyen; Thuy Hong Nguyen (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
Academic motivation encourages people to participate in learning activities and directs, maintains, and determines the intensity of learning behaviors. Therefore, nursing students require high-quality academic motivation to continuously and effectively improve their medical knowledge and skills continuously and effectively. This study measures nursing students' academic motivation and identifies the associated factors. A cross-sectional study design was used. The total sample included 237 undergraduate nursing students. The data were collected from October to November 2022 in a public university located in Southwestern Vietnam. The level of academic motivation was measured using the Vietnamese version of the Academic Motivation Scale. The data were analyzed using the independent Student's t-tests, ANOVA, Pearson's correlation, and regression analysis. The study showed that nursing students had high academic motivation. However, there were still more than one-third of students (39.3%) whose quality of academic motivation was not good. Through simple linear regression analysis, it showed that appropriate training regulations of the school; getting support/questions answers or good examples in learning from lecturers/medical staff at the clinical practice site; joining a club about learning; intending to teach in the field of nursing, ability to deal with difficulties were the factors that affect nursing students' academic motivation. Many associated factors influence the academic motivation of nursing students. Further effective interventions are needed to address this issue.